The importance of public relations in managing humanitarian crises-the Baghdad health Al-Karkh directorate's management of Covid9 through public relations (Journal of Imam Al-Kadhim College, 2023)
Abstract:The aim of the research is to identify the importance of public relations in managing humanitarian crises and the role it plays in activating communication activities with the public in the specialized institutions, working under crisis conditions, and the extent of its readiness for that confrontation through its various practices and activities before the crisis and the flexibility of those practices and activities during the crisis. Then looking at the obstacles and the  negatives that arise after the end of the crisis, and the practical application of the research was carried out in the Baghdad Health Department, Al-Karkh, to verify the importance of public relations in managing humanitarian crises, where a questionnaire was distributed to a sample of (35) workers in the media sector, and it was retrieved from them (33) a questionnaire. Their answers to the questionnaire paragraphs were analyzed and the frequencies of those paragraphs identified in order to be able to determine the extent to which public relations activities contribute to dealing with crises. Organizational structure in the media sector. It is supervised by the general administration and is practically linked to it. The research suggested a number of recommendations, the most important of which was the need to develop the media sector in the department, which includes most of the functions of public relations and crisis management.
Keywords: public relations, communication activities, humanitarian crisis management